G-108 Some HIV-1 virions are more equal than others: Mosaics of Envs on individual HIV virions as evaluated with flow virometry. (January 2016) - Arakelyan, Anush; Fitzgerald, Wendy; King, Deborah; Barreto-de-Souza, Victor; Zicari, Sonia; Grivel, Jean-Charles; Shattock, Robin; Margolis, Leonid
Abstract : The ability of HIV to infect cells depends on the "functional" conformation of envelope spike glycoproteins (Env). However, other non-functional Env conformations are also displayed on virions. Determination of whether functional and non-functional forms of Env are co-displayed requires analysis of individual virions. We have applied a recently developed "flow virometry" to probe the conformation of Envs on single virions. Individual HIV virions were captured with 15-nm magnetic nanoparticles (MNPs) decorated with anti-Env antibodies that recognize different epitopes of either the "functional" or non-functional Envs (monomeric, uncleaved gp160, or "stumps"). The MNP-virions complexes were isolated in a magnetic field. Our technology distinguished virions that were homogenous or mosaic with respect to functional and non-functional forms of Env. The majority of virions were not mosaic: if an HIV-1 virion has at least one functional spike, there is a low probability that this virion also carries defective spikes or gp41 stumps. A small fraction of virions was highly mosaic and carried various combinations of Env monomers, uncleaved gp160, stumps, and trimeric Envs. These virions do not contribute to the infection of human lymphoid tissue ex vivo, thus confirming the results of flow virometry. Flow virometry demonstrated that on the majority of virions in an HIV preparation there are either exclusively functional trimeric Envs or predominantly defective Envs. Only a relatively small fraction of virions were mosaic with respect to carrying both functional and nonfunctional Envs. The contribution of this fraction to HIV infection of human tissue is small. This all-or-nothing viral strategy is likely to facilitate HIV evasion of the immune response subverting the focus of humoral responses into the generation of non-neutralizing antibodies at no cost to infectious virions. In general, flow virometry provides new insight in the structure of HIV virions that may be important for the development of anti-HIV-1 vaccines.